2018
DOI: 10.1186/s12874-018-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the normalization of complex interventions: part 2 - validation of the NoMAD instrument for assessing implementation work based on normalization process theory (NPT)

Abstract: IntroductionSuccessful implementation and embedding of new health care practices relies on co-ordinated, collective behaviour of individuals working within the constraints of health care settings. Normalization Process Theory (NPT) provides a theory of implementation that emphasises collective action in explaining, and shaping, the embedding of new practices. To extend the practical utility of NPT for improving implementation success, an instrument (NoMAD) was developed and validated.MethodsDescriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
231
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(239 citation statements)
references
References 48 publications
5
231
2
1
Order By: Relevance
“…The questionnaire included a socio‐demographic section, a standardised validated instrument (NoMAD) and space for free‐text comments. The NPT‐based instrument NoMAD (Finch et al, ; Rapley et al, ) measured individual's opinions on the levels of IRIS embeddedness in daily work. The NoMAD instrument consists of two sections: (a) three general questions about normalisation of the practice (a 10‐point scale from 0 ‘Not at all’ to 10 ‘Completely’) and (b) 23 items reflecting the four NPT constructs (Finch et al, ) (a 5‐point scale from 1 ‘Strongly disagree’ to 5 ‘Strongly agree’ with 0 for ‘Not relevant to me’).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire included a socio‐demographic section, a standardised validated instrument (NoMAD) and space for free‐text comments. The NPT‐based instrument NoMAD (Finch et al, ; Rapley et al, ) measured individual's opinions on the levels of IRIS embeddedness in daily work. The NoMAD instrument consists of two sections: (a) three general questions about normalisation of the practice (a 10‐point scale from 0 ‘Not at all’ to 10 ‘Completely’) and (b) 23 items reflecting the four NPT constructs (Finch et al, ) (a 5‐point scale from 1 ‘Strongly disagree’ to 5 ‘Strongly agree’ with 0 for ‘Not relevant to me’).…”
Section: Methodsmentioning
confidence: 99%
“…Survey responses were downloaded from the Online Surveys platform (Jisc, ), cleaned and imported into Stata 15. Counts and frequencies were used to describe the sample and summarise NoMAD responses (Finch et al, ; Rapley et al, ). The customised 23‐item NoMAD instrument demonstrated a very good reliability of the whole scale (Cronbach α = 0.94) and the four NPT constructs (coherence α = 0.86, cognitive participation α = 0.86, collective action α = 0.80, reflexive monitoring α = 0.83) (DeVellis, ; Tavakol & Dennick, ).…”
Section: Methodsmentioning
confidence: 99%
“…Respondents completed the NoMAD questionnaire. 27,32 NoMAD provides a tool based on NPT, for the assessment of the work of implementation from the perspective of those involved in working with the practice innovation. For analyses reported in this paper, the questionnaire comprised 4-7 items for each of the four generative processes associated with normalisation: coherence, cognitive participation, collective action and reflexive monitoring (20 items in total).…”
Section: Methodsmentioning
confidence: 99%
“…Items are rated on a 5point Likert scale from 1 (strongly agree) to 5 (strongly disagree). Initial validation demonstrated that the NoMAD has good face validity, construct validity, and internal consistency (39).…”
Section: Implementation Predictorsmentioning
confidence: 99%